The Cambridge encyclopedia of language - Crystal, David 1941- (Cambridge University Press, 2010)
"This new, thoroughly revised edition of the acclaimed Cambridge Encyclopedia of Language incorporates the major developments in language study which have taken place since the mid-1990s. Two main new areas have been added: the rise of electronic communication in all its current forms, from email to tweeting, and the crisis affecting the world's languages, of which half are thought to be so seriously endangered that they will the out this century."--Book jacket.